A study for the development of new compound gasification process of waste plastics and sludge - Sadakata, M.
A conventional gasification process of waste polyvinyl chloride (PVC) has a serious problem of producing a poisonous hydrogen chloride (HCl) which causes corrosion of a reactor wall or a heat exchanger. On the other hand, a gasification of a drainage sludge is sometimes meaningless since a calorific value of the produced gas is too low to be used as a gas fuel. In order to solve these problems, a new compound gasification process in which PVC and dry sludge are mixed and gasified together in the fluidized bed was proposed and tested by using a small scale fluidized bed. The important results were as follows : 1) Hydrogen chloride gas (HCl) from PVC was significantly removed by slaked lime in the sludge when mole ratio of slaked lime to HCl was 5 : 1 in the bed. A slaked lime is often added to the sludge as a flocculant in the desiccation process. 2) A calorific value of produced gas from PVC was 6000 to 7000 Kcal/NM3 whilst that from sludge was around 2000 Kcal/Nm3 without slaked lime and 4000 to 5000 Kcal/Nm3 with slaked lime in the gasification temperature between 600°C to 800°C.